PENERAPAN METODE SOSIODRAMA PADA SENTRA BERMAIN PERAN - Uswatun Hasanah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Keagamaan Islam UNUGHA Cilacap, 2022)
The real world of the child is the world of play, play has very important benefits for the growth and development of the child, both psychic and physical child, through play children test their guesses about how the world functions, the child can explore and experiment with various things around him. Role-playing is not an easy activity, children who often practice with drama games are often those who succeed in life as adults. Sociodrama activities at the role-playing center at Yabakii Kesugihan Kindergarten are held from 07.30 to 10.00, in class B3 the role center learning is carried out one month twice face-to-face, namely every month of the first week and the third week with a total of 17 students. Sociodrama Activities in Role-Playing Center Learning Develop abstract, language, Social Emotional thinking skills, connect the knowledge that children already have with new knowledge, using role-playing tools that are small in size or according to the actual size.